'Not just right' experiences and incompleteness in body dysmorphic disorder. (January 2017) - Summers, Berta J.; Matheny, Natalie L.; Cougle, Jesse R.
Abstract: The current studies examined the role of 'not just right' experiences (NJREs) and incompleteness (INC) in body dysmorphic disorder (BDD). In Study 1, a clinical BDD sample endorsed more severe NJREs than healthy controls, when controlling co-occurring symptoms of depression and anxiety. In Study 2, INC predicted reactivity to an in vivo task designed to evoke BDD-related concerns in an unselected sample. Study 3 demonstrated a positive relationship between INC and BDD symptom severity in a community sample. Study 4 examined in vivo sensory NJRE tasks and INC in a sample high and low in BDD symptoms. The high symptom group reported greater INC and reactivity to a visual NJRE task than their low symptom counterparts, when controlling for co-occurring symptoms of depression, anxiety, and OC symptoms. No group differences were observed for tasks assessing auditory and tactile NJREs. These studies demonstrate a unique relationship between INC/NJREs and BDD. Highlights: We examined sensory-perceptual disturbances in body dysmorphic disorder (BDD). Self-report and in vivo assessments of sensory phenomena and BDD symptoms were used. 'Not just right' experiences and incompleteness were related to BDD symptoms. Relationships were largely independent of symptoms of depression, anxiety, and OCD.